Gynecological Insights into Lynch Syndrome—A Comprehensive Review of Cancer Screening and Prevention - Elena Chitoran; Roxana-Elena Bohiltea; Vlad Rotaru; Cristiana-Elena Durdu; Madalina-Nicoleta Mitroiu; Laurentiu Simion (Medicina)
Lynch syndrome, one of the most common genetic syndromes predisposing to cancer, is associated with a series of malignant conditions, among which the most frequent is colorectal cancer, but gynecologic cancers (especially endometrial) are also quite common. Despite the significant progress made in understanding this condition over time, there are still aspects in managing this condition that have not demonstrated clear benefits. This article aims to summarize the recommendations of international societies and present the latest developments in managing Lynch syndrome, focusing on gynecologic cancer screening and possible prevention strategies. Advances in genetic testing procedures and discoveries related to the association between oncological pathology frequency and the affected pathogenic variant type will probably lead to personalized medicine focused on the individual patient in the coming years. Although various screening methods for gynecological cancers in patients with Lynch syndrome have been used over time, they have not shown significant survival benefits. This highlights the need for studying and implementing new screening and diagnostic methods, which have been under investigation in recent years and are mentioned in this article.